Detailed Facies Analysis of Assedjefar Formation in Al Awaynat Area, Murzuq Basin, Southwestren Libya - Elzidani, Emhmed; Kamel, Saad; Ahmad , Mahmoud (Journal of Pure & Applied Sciences, 2021)
This Facies analyses of rocks are a powerful tool that might be used to reconstruct geological events, environmental conditions, and depositional environments of the rocks. This study provides detailed facieses analyses of the Assedjefar Formation based on petrography, fossil contents, and hand specimens. Furthermore, 29 thin sections have been made from selected samples of the studied sequence. A group of 33 repeated fine facieses has been defined throughout the studied sections. A 25 facies of them are fine limestone facieses, and 8 of them are fine facieses of clastic rocks. Furthermore, the fine limestone facieses were classified into 6 typical facieses, without repetition, and ranged from mudstone to grainstone with various grain types. 2 sedimentary zones are determined for limestones deposits and they are restricted platform interior and Open Marine platform interior. While the fine clastic facieses were deposited within 3 sedimentary zones and whish are marine, Mixed marine-fluvial, and fluvial.